Biometria ocular na espécie Cebus apella - Estanislau, Cristiane de Abreu [UNESP] (2014)
The aim of this study was to determine the ocular dimensions of capuchin monkeys using ultrasound A and keratometry, determining the refractive power of the IOL formulas employing third and fourth generation. Were used 18 animals (36 eyes) of the species Cebus apella. The calculation of intraocular lens was performed using the Holladay IOL Consultant ® and EyeCalculator ® 6.0 software. Holladay 2, Hoffer Q, and Haigis formulas were employed to do the calculus and determin lenses with an average refractive power of 29.43 D; 31.25 D and 46.71 D, respectively. No statistical difference was observed between the lens dioptric values calculated by formulas Holladay 2 and Haigis; however, we could see statistical difference between groups when the the formula Hoffer Q was applied, resulting in more powerful lenses. The reviews of ocular biometric parameters and the lens power calculated by the same formula showed neither significant differences between males and females, or between the right and left eyes of each animal